Repeated epidural delivery of Shinbaro2: effects on neural recovery, inflammation, and pain modulation in a rat model of lumbar spinal stenosis - Hong, Jin Young; Yeo, Changhwan; Kim, Hyun; Lee, Junseon; Jeon, Wan-Jin; Lee, Yoon Jae; Ha, In-Hyuk (Frontiers in Pharmacology, 2024)
The choice of treatment for lumbar spinal stenosis (LSS) depends on symptom severity. When severe motor issues with urinary dysfunction are not present, conservative treatment is often considered to be the priority. One such conservative treatment is epidural injection, which is effective in alleviating inflammation and the pain caused by LSS-affected nerves. In this study, Shinbaro2 (Sh2), pharmacopuncture using natural herbal medicines for patients with disc diseases, is introduced as an epidural to treat LSS in a rat model. The treatment of primary sensory neurons from the rats' dorsal root ganglions (DRGs) with Sh2 at various concentrations (0.5, 1, and 2 mg/mL) was found to be safe and non-toxic. Furthermore, it remarkably stimulated axonal outgrowth even under H2O2-treated conditions, indicating its potential for stimulating nerve regeneration. When LSS rats received epidural injections of two different concentrations of Sh2 (1 and 2 mg/kg) once daily for 4 weeks, a significant reduction was seen in ED1 + macrophages surrounding the silicone block used for LSS induction. Moreover, epidural injection of Sh2 in the DRG led to a significant suppression of pain-related factors. Notably, Sh2 treatment resulted in improved locomotor recovery, as evaluated by the Basso, Beattie, and Bresnahan scale and the horizontal ladder test. Additionally, hind paw hypersensitivity, assessed using the Von Frey test, was reduced, and normal gait was restored. Our findings demonstrate that epidural Sh2 injection not only reduced inflammation but also improved locomotor function and pain in LSS model rats. Thus, Sh2 delivery via epidural injection has potential as an effective treatment option for LSS.